2015
DOI: 10.1682/jrrd.2014.08.0189
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular control of curved walking in people with stroke: Case report

Abstract: Abstract-People are required to adapt their basic walking pattern to turn and change directions safely for activities of daily living. This case study describes the changes in neuromuscular control among individuals with stroke on walking paths of different curvatures. Two men with hemiparetic stroke and one control subject walked along a straight, wide curved, and tight curved pathway while muscle activation of the medial and lateral gastrocnemius was recorded, along with the trajectory of the center of press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The Timed Up and Go test (Podsiadlo and Richardson 1991) and timed 10 m Walk test were used to assess over-ground walking mobility, speed, and endurance. The Timed Up and Go test, in addition to the extra demand of standing from a seated position, also required unique demands on neural processes involved in the control of medial–lateral stability for the purpose of turning around which are not required for the 10 m Walk test (Chisholm et al 2015). The same individual, to limit inter-rater variability, performed all clinical walking tests.…”
Section: Methodsmentioning
confidence: 99%
“…The Timed Up and Go test (Podsiadlo and Richardson 1991) and timed 10 m Walk test were used to assess over-ground walking mobility, speed, and endurance. The Timed Up and Go test, in addition to the extra demand of standing from a seated position, also required unique demands on neural processes involved in the control of medial–lateral stability for the purpose of turning around which are not required for the 10 m Walk test (Chisholm et al 2015). The same individual, to limit inter-rater variability, performed all clinical walking tests.…”
Section: Methodsmentioning
confidence: 99%
“…Nine studies measured turning on the spot[10, 20, 37, 41, 46, 48, 52, 66, 67], three studies were radius circle or semicircle[33, 36, 57]. The maximum and average length of approach path was 7 m and 3.33 m, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum and average length of approach path was 7 m and 3.33 m, respectively. Turn direction was set for both sides in 26 studies[9, 10, 27, 33, 34, 36, 37, 39-41, 45-49, 51, 52, 54, 56, 57, 62, 64-66, 68, 69], and 16 studies limited either side[11, 19, 20, 29, 32, 35, 38, 42-44, 59-61, 67, 70, 71]. The formalized task was only TUG with 7 studies[11, 28, 30, 40, 58, 62, 63], 11 studies including instrumented TUG[50, 55, 59, 68].…”
Section: Resultsmentioning
confidence: 99%
“…However, a previous study reported that walking along a curved path implies a different spatiotemporal parameter of muscle activation compared with straight walking in humans [16][17][18][19]. After the studies, several researchers have reported on curved walking in hemiparetic individuals [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Godi et al [20] reported the velocity of curved walking was not significantly smaller in hemiparetic patients compared with linear walking. Two other studies examined the neuromuscular strategies in the paretic leg during curved walking for persons with stroke [21,22]. Indeed, there is a lack of studies comparing linear walking and curved path walking in stroke surivors.…”
Section: Discussionmentioning
confidence: 99%